Effectiveness of Pneumococcal Conjugate Vaccine in Reducing Childhood Pneumonia: A Comprehensive Literature Review - Praditina, Rr. Wening Gelar; Aprilia, Asti; Yulyanti, Desi (Medical and Health Journal, 2025)
Background: Pneumonia remains the leading cause of morbidity and mortality among children under five worldwide, with Streptococcus pneumoniae and Haemophilus influenzae identified as the most common etiological agents. The high disease burden, particularly in low- and middle-income countries, underscores the urgent need for effective prevention strategies. The Pneumococcal Conjugate Vaccine (PCV) has demonstrated substantial impact in reducing pneumonia incidence and invasive pneumococcal disease globally, and has been included in Indonesia’s national routine immunization program since 2022. Objective: This literature review aims to synthesize current evidence on the effectiveness of PCV in reducing childhood pneumonia morbidity and mortality, evaluate its safety profile, and discuss implications for immunization policy and program implementation in Indonesia and globally. Methods: A narrative literature review was conducted using data from peer-reviewed journals, WHO reports, and national health surveys published between 2010 and 2025. Databases searched included PubMed, Scopus, and Google Scholar, using keywords “pneumococcal conjugate vaccine,” “effectiveness,” “childhood pneumonia,” and “immunization program.” Studies meeting inclusion criteria—randomized controlled trials, cohort studies, case-control studies, and meta-analyses—were analyzed and synthesized. Results: Evidence from multiple countries, including the United States, France, Israel, South Africa, Argentina, and Indonesia, consistently demonstrates significant reductions in pneumonia hospitalizations, invasive pneumococcal disease incidence, and mortality among children following PCV introduction. PCV-13 and PCV-15 have shown broad serotype coverage and sustained impact. Co-administration of PCV with other routine vaccines has been proven safe, with no increase in adverse events following immunization (AEFI). Conclusion: PCV is an effective and safe intervention for reducing the burden of childhood pneumonia and invasive pneumococcal disease. Nationwide implementation in Indonesia has the potential to substantially decrease pneumonia-related mortality in children under five. Continuous surveillance, serotype monitoring, and program evaluation are essential to maximize vaccine benefits and inform future immunization policies.